RENCANA PENGEMBANGAN TANAMAN KOPI DI WILAYAH TINANGKUNG SELATAN BERDASARKAN PENDEKATAN KESESUAIAN LAHAN - Sariani, Sariani; Ladonu, Moh. Ilham; Puspapratiwi, Dian; Katili, Hidayat Arismunandar (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Effective agricultural land use necessitates careful and intensive management that considers the unique characteristics of each plot, as these can vary significantly. Given the extensive information on land suitability for coffee plantations in the Tinangkung Selatan sub-district, research is essential to assess the area's substantial potential for coffee cultivation. The primary aim of this study is to determine the suitability of land for coffee plants in situ within the South Tinangkung District. A quantitative descriptive survey approach was employed, matching actual land conditions with coffee land suitability criteria. Analysis of eight sample points revealed three suitability classes: moderately suitable (S2), marginally suitable (S3), and unsuitable (N). At point 2, the land was classified as moderately suitable (S2) for coffee cultivation, covering 567.03 ha, influenced by moderate soil depth, base saturation, very low nitrogen levels, and a gentle slope. The marginally suitable (S3) criteria were affected by nitrogen levels (point 1), altitude (point 3), base saturation, organic carbon, and nitrogen levels (point 4), encompassing 7,898.87 ha. The unsuitable class (N) was identified at points 5, 6, 7, and 8, covering 6,098.42 ha, primarily due to altitude. Improvement efforts indicate potential land suitability, with 2,049.16 ha classified as moderately suitable (S2), 7,479.89 ha as marginally suitable (S3), and 5,035.28 ha as unsuitable (N). Engaging stakeholders, including government, research institutions, communities, and the private sector, is crucial for managing this land effectively, particularly in restoring and enhancing the function of less productive or degraded areas to optimize their potential.